Impacts of valproic acid on systemic bone loss associated with experimental model of rheumatoid arthritis in rats - Shaema Mohammed Ali Mohammed; Adeeb A Al-Zubaidy (Medical Journal of Babylon, 2023)
Background: Valproic acid (VA) is a compound used for many neurological disorders, which is also known as a histone deacetylase inhibitor. The impacts of VA on adjuvant-induced arthritis (AIA) in rats were investigated. Objectives: To investigate the possible osteoprotective and anti-inflammatory effects of VA in rheumatoid arthritis (RA). Materials and Methods: AIA was achieved through subdermal injection of complete Freund’s adjuvant (CFA) into the rat hindpaw. Forty Swiss albino rats were recruited in this study. These rats were divided into four groups: the normal control group received 0.1 mL phosphate buffer saline intraperitoneally each day, the positive control group received 0.75 mg/kg intraperitoneal once weekly dose of methotrexate, the AIA group received CFA without treatment, and the VA group received 300 mg/kg/day intraperitoneal dose of VA. Statistical analysis was done, and a P value of less than 0.05 was considered as statistically significant. Results: VA (300 mg/kg body weight) administered intraperitoneally could significantly reverse the effect of adjuvant arthritis on bone mineral density and bone mineral content in addition to an improvement in bone formation markers (osteoprotegerin, osteoprotegerin/RANKL ratio). Serum levels of tumor necrosis factor and interleukin 1b were significantly reduced by VA treatment. Reduced serum malondialdehyde with the elevated superoxide dismutase level was also achieved. Conclusion: These findings support the evidence that VA has a positive effect on bone anabolism and its anti-inflammatory properties could be considered as a bonus in inflammatory disorders induced bone loss such as RA.